Powder metallurgy brake pad material, preparation method and brake pad
By adding tantalum carbide, aluminum powder and N-β-hydroxyethylethylenediamine triacetic acid to the rail transit train gate material, the interface bonding and density of powder metallurgy materials are improved, and the material heat during braking of high-speed trains is solved The problem of decay achieves efficient friction performance and low wear.
Patent Information
- Application Number
- CN202410978472.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-22
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-07-22
AI Technical Summary
During high-speed braking, the friction performance of existing rail transit train gate sheet materials rapidly declines due to the thermal decay of copper materials and the poor bonding force of added components, making it difficult to meet the heat resistance requirements of high-speed trains.
Using powder metallurgical materials, tantalum carbide and aluminum powder are added as flux promoters, the interface metallographic and density are improved through the sintering process, combined with N-β-hydroxyethylethylenediamine triacetic acid to inhibit metal oxides, ball milling and spray drying processes are improved Component binding and sintering density.
Maintain excellent friction performance and low wear when braking in high-speed trains, extend service life, and meet the heat fading needs of high-speed trains.
Smart Images

Figure CN119120980A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a rail transit train brake device, and in particular to a powder metallurgy brake pad material, a preparation method and a brake pad. Background Art
[0002] The brake pad is a part of the braking system of a rail transit train. When the train brakes, the brake pad is attached to the brake disc of the wheel, slowing down the rotation speed of the wheel through friction to achieve the braking effect.
[0003] Currently, copper-based powder metallurgy materials with high mechanical strength and good thermal conductivity are mostly used as materials for brake pads. In addition, graphite, molybdenum disulfide, zirconium dioxide, and silicon dioxide are added to copper powder to improve the friction coefficient and friction performance.
[0004] However, during the manufacturing process, the kinetic energy of the wheel is converted into internal energy, and the temperature of the brake pad rises rapidly. The copper as the matrix suffers from thermal decay under the high load and high temperature of the wheel. At the same time, added components such as graphite, molybdenum disulfide, zirconium dioxide, and silicon dioxide have poor wettability with copper and weak bonding force, and are prone to falling off, resulting in rapid decay of friction performance in a hot environment. The continuous manufacturing time is limited and short. For the overload design required for high-speed train braking, the heat decay resistance of the brake pad needs to be further improved to meet the future research and development needs of high-speed trains. Summary of the invention
[0005] In order to better adapt to and meet the needs of high-speed braking, powder metallurgy brake pad materials, preparation methods and brake pads are provided.
[0006] The above first invention objective of the present invention is achieved through the following technical solutions: A powder metallurgy brake pad material is obtained by sintering powder, and includes the following raw materials in parts by weight: 67-70 parts of electrolytic copper powder; 12-17 parts of iron powder; Tungsten 5-9 parts; 12-18 parts of flake graphite; Molybdenum disulfide 7-9 parts; 5-8 parts of zirconium dioxide; 7-11 parts of nano silicon dioxide; Tantalum carbide 5-8 parts.
[0007] By adopting the above technical scheme, tantalum carbide added to the raw material improves the interface metallographic structure between tantalum carbide and other metal alloys during the high-temperature sintering process of the raw material, thereby enhancing the bonding of the components in the powder metallurgy brake pad material and providing the powder metallurgy material with deformation resistance at high temperatures. When the high-speed train brakes and the brake pad temperature rises rapidly, the components in the powder metallurgy brake pad material are tightly bonded and not easily separated, thereby suppressing the thermal decay of the friction performance of the powder metallurgy brake pad material, thereby ensuring the excellent friction performance and low wear of the brake pad under high-speed braking.
[0008] Optionally, 5-8 parts of fluxing agent are also included, and the fluxing agent is micron-grade aluminum powder.
[0009] By adopting the above technical solution, aluminum powder is used as a flux. During the sintering process, aluminum melts first and infiltrates into the blank. The liquid surface tension of the molten aluminum causes adjacent raw material particles to move closer together and form a eutectic under the promotion of the molten aluminum, making the powder sintered more densely. On the other hand, the residual aluminum is oxidized to form aluminum oxide under high-temperature friction, which promotes the formation of a friction film on the brake pad, thereby increasing the friction coefficient of the brake pad material at high speed and reducing the amount of wear.
[0010] Optionally: the iron powder is foamed iron powder.
[0011] By adopting the above technical solution, the foamed iron powder can improve the friction performance of the powder metallurgy brake pad material and reduce the braking noise.
[0012] The above second invention objective of the present invention is achieved through the following technical solutions: The method for preparing a powder metallurgy brake pad material comprises the following steps: S1: weighing the raw materials according to the usage ratio and mixing them evenly to obtain a mixture; S2: Add the mixture, medium and N-β-hydroxyethylethylenediaminetriacetic acid into a ball mill and grind them. S3: The slurry obtained by ball milling is spray dried to obtain powder particles. S4: filling the powder particles into a pressing mold and pressing to obtain a green body; S5: sintering the green body to obtain a powder metallurgy brake pad material; The medium is ethanol and polyethylene glycol, and the relative molecular weight distribution of polyethylene glycol is 1000-1200. The mass ratio of the mixture, ethanol and polyethylene glycol is 100:(56-65):(15-20).
[0013] By adopting the above technical scheme, N-β-hydroxyethylethylenediaminetriacetic acid is dissolved in ethanol during the ball milling process, which inhibits and eliminates metal oxides produced by high temperature and extrusion stress during the ball milling process, especially iron oxides carried on the surface of iron powder or foamed iron powder, thereby avoiding loose oxides from affecting the composition of spray granulation and subsequent sintering eutectic body, so that the eutectic body has good strength after cooling and is more tightly combined with unmelted solid powder particles, thereby providing the powder metallurgy brake pad material with heat decay resistance.
[0014] Optionally, the mass ratio of the mixture to N-β-hydroxyethylethylenediaminetriacetic acid is 100:(0.3-0.5).
[0015] By adopting the above technical solution, the amount of N-β-hydroxyethylethylenediaminetriacetic acid in the present application is preferably 0.3-0.5wt% of the mixture. Optional: The particle size of S3 powder is 100 to 220 μm.
[0016] Optionally, the green body is obtained by compounding powders with different particle sizes, and the particle size distribution is as follows: 210±10μm particle size accounts for 46wt%, 150±10μm particle size accounts for 32wt%, and 110±10μm particle size accounts for 22wt%.
[0017] By adopting the above technical solution, the powder metallurgy brake pad material blank before sintering is obtained by mixing and pressing powders of three particle sizes. The mixed combination has faster sintering densification and higher densification degree, so that the powder metallurgy brake pad material has better resistance to thermal decay.
[0018] The third object of the present invention is achieved by the following technical solutions: The brake pad is made from the above powder metallurgy brake pad material.
[0019] By adopting the above technical solution, the brake pad has heat decay resistance. When the high-speed brake pad heats up rapidly, it still maintains an excellent friction coefficient and low wear, and is better suitable for and meets high-speed braking needs.
[0020] In summary, this application has at least the following beneficial effects: 1. Tantalum carbide added to the raw materials improves the interface metallographic phase of the sintered body, enhances the bonding of the components in the powder metallurgy brake pad material, and provides the powder metallurgy material with high temperature resistance to deformation. When the high-speed train brakes and the brake pad temperature rises rapidly, the components in the powder metallurgy brake pad material are tightly bonded and not easy to separate, inhibiting the thermal decay of the friction performance of the powder metallurgy brake pad material, thereby ensuring the excellent friction performance and low wear of the brake pad under high-speed braking; 2. Use an appropriate amount of aluminum powder as a flux to increase the sintering density and promote the formation of the brake pad friction film, thereby increasing the friction coefficient of the brake pad material at high speed and reducing the amount of wear; 3. During the preparation of powder metallurgy brake pad materials, raw materials, medium, and N-β-hydroxyethylethylenediaminetriacetic acid are ball-milled together to inhibit and eliminate metal oxides generated by high temperature and extrusion stress during ball milling, and to prevent loose oxides from affecting the composition of spray granulation and subsequent sintering eutectic bodies. After cooling, the eutectic body has good strength and is more tightly combined with unmelted solid powder particles, thus providing the powder metallurgy brake pad material with heat decay resistance; 4. The green body of the powder metallurgy brake pad material before sintering is obtained by mixing and pressing powders of three particle sizes. The mixed combination has faster sintering densification and higher densification degree, making the powder metallurgy brake pad material better in thermal decay resistance. BRIEF DESCRIPTION OF THE DRAWINGS Figure 1 It is a schematic diagram of the structure of the gate piece.
[0022] Figure 2 This is an exploded view of the gate piece.
[0023] Reference numerals: 1. Steel back; 2. Friction body; 3. Fixed shaft; 4. Circlip. DETAILED DESCRIPTION
[0024] Example 1 A powder metallurgy brake pad material, the raw materials of which include electrolytic copper powder, iron powder, tungsten, flaky graphite, molybdenum disulfide, zirconium dioxide, nano silicon dioxide, tantalum carbide and fluxing agent.
[0025] The particle size of electrolytic copper powder is 8μm; the iron powder is foamed iron powder with a particle size of 5μm; the particle size of tungsten is 4μm; the particle size of flaky graphite is 9μm; the particle size of molybdenum disulfide is 2μm; the particle size of zirconium dioxide is 2μm; the particle size of nano-silicon dioxide is 90nm; the particle size of tantalum carbide is 1μm; the flux is aluminum powder with a particle size of 2μm.
[0026] The preparation method of powder metallurgy brake pad material is as follows: S1: 69 kg of electrolytic copper powder, 16 kg of iron powder, 8.3 kg of tungsten, 16.5 kg of flaky graphite, 8.1 kg of molybdenum disulfide, 7.4 kg of zirconium dioxide, 10.3 kg of nano silicon dioxide, 7.2 kg of tantalum carbide and 6.5 kg of flux are mixed uniformly to obtain a mixture; S2: Add the mixture, medium and N-β-hydroxyethylethylenediaminetriacetic acid into a ball mill and grind until the solid particle size is 17.5±2.5μm. S3: The slurry obtained by ball milling is divided into three parts, and each part is spray dried to obtain a powder with a particle size of 210±10μm, a powder with a particle size of 150±10μm, and a powder with a particle size of 110±10μm; S4: 46 wt% of powder with a particle size of 210±10 μm, 32 wt% of powder with a particle size of 150±10 μm, and 22 wt% of powder with a particle size of 110±10 μm are mixed, and then filled into a pressing mold for pressing to obtain a green body; S5: Sintering the green body to obtain a powder metallurgy brake pad material, the sintering temperature being 920° C.; The medium is ethanol and polyethylene glycol, and the relative molecular weight distribution of the polyethylene glycol is 1000-1200.
[0027] The mass ratio of the mixture, ethanol, polyethylene glycol and N-β-hydroxyethylethylenediaminetriacetic acid is 100:61:17.5:0.42.
[0028] Example 2 A powder metallurgy brake pad material, which differs from Example 1 in that the raw materials do not contain a fluxing agent, that is, the mixture in S1 is a mixture of electrolytic copper powder, iron powder, tungsten, flaky graphite, molybdenum disulfide, zirconium dioxide, nano silicon dioxide, and tantalum carbide.
[0029] Comparative Example 1 A powder metallurgy brake pad material, which differs from Example 1 in that the raw material does not contain tantalum carbide, that is, the mixture in S1 is mixed with electrolytic copper powder, iron powder, tungsten, flaky graphite, molybdenum disulfide, zirconium dioxide, nano silicon dioxide, and a flux.
[0030] Comparative Example 2 A powder metallurgy brake pad material, which differs from Example 1 in that the raw materials do not contain tantalum carbide and flux, that is, the mixture in S1 is a mixture of electrolytic copper powder, iron powder, tungsten, flaky graphite, molybdenum disulfide, zirconium dioxide, and nano-silicon dioxide.
[0031] Example 3 A powder metallurgy brake pad material, which is different from Example 1 in that the iron powder in the raw material is ordinary iron powder.
[0032] Example 4 A powder metallurgy brake pad material, which differs from Example 1 in that S2 is to add a mixed material and a medium into a ball mill for ball milling, and the medium is ethanol and polyethylene glycol.
[0033] Example 5 A powder metallurgy brake pad material, which differs from Example 1 in that the mass ratio of the mixed material to N-β-hydroxyethylethylenediaminetriacetic acid in S2 is 100:0.1.
[0034] Example 6 A powder metallurgy brake pad material, which differs from Example 1 in that the mass ratio of the mixed material to N-β-hydroxyethylethylenediaminetriacetic acid in S2 is 100:0.3.
[0035] Example 7 A powder metallurgy brake pad material, which differs from Example 1 in that the mass ratio of the mixed material to N-β-hydroxyethylethylenediaminetriacetic acid in S2 is 100:0.5.
[0036] Example 8 A powder metallurgy brake pad material, which differs from Example 1 in that the mass ratio of the mixed material to N-β-hydroxyethylethylenediaminetriacetic acid in S2 is 100:0.8.
[0037] Example 9 A powder metallurgy brake pad material, which differs from Example 1 in that the powder particle size distribution in S4 is 110±10 μm.
[0038] Example 10 A powder metallurgy brake pad material, which differs from Example 1 in that the powder particle size distribution in S4 is 210±10 μm.
[0039] Embodiment 11 A powder metallurgy brake pad material, which differs from Example 1 in that the mixed materials in S1 are as follows: 67kg electrolytic copper powder, 12kg iron powder, 5kg tungsten, 12kg flaky graphite, 7kg molybdenum disulfide, 8kg zirconium dioxide, 7kg nano silicon dioxide, 5kg tantalum carbide, and 5kg flux.
[0040] The mass ratio of the mixed material, ethanol, polyethylene glycol, and N-β-hydroxyethylethylenediaminetriacetic acid in S2 is 100:56:15:0.3.
[0041] Example 12 A powder metallurgy brake pad material, which differs from Example 1 in that the mixed materials in S1 are as follows: 70kg electrolytic copper powder, 17kg iron powder, 9kg tungsten, 18kg flaky graphite, 9kg molybdenum disulfide, 5kg zirconium dioxide, 11kg nano silicon dioxide, 8kg tantalum carbide, and 8kg flux.
[0042] The mass ratio of the mixed material, ethanol, polyethylene glycol, and N-β-hydroxyethylethylenediaminetriacetic acid in S2 is 100:65:20:0.5.
[0043] The average friction coefficient and wear amount at braking speeds of 80 to 350 km / h obtained at different speeds were tested for Examples 1-11 and Comparative Examples 1-2 according to the C.6 procedure in TJ / CL307-2019 "Interim Technical Conditions for EMU Brake Pads". The test results are shown in Table 1 below.
[0044] Note: The wear amount is the wear amount compared with that before the braking procedure as specified in the C.6 procedure in TJ / CL307-2019 "Interim Technical Conditions for EMU Brake Pads".
[0045] Table 1. Average friction coefficient and wear amount results of Examples 1-12 and Comparative Examples 1-2 In combination with Table 1, Examples 1-2 and Comparative Examples 1-2, Example 1 adds tantalum carbide to the raw material compared to Comparative Example 1, and Example 2 adds tantalum carbide to the raw material compared to Comparative Example 2. During the high-temperature sintering process of the raw material, tantalum carbide improves the interface metallographic phase with other metal alloys during the sintering process, enhances the bonding of the components in the powder metallurgy brake pad material, and provides the powder metallurgy material with deformation resistance at high temperature, so that when the high-speed train brakes and the brake pad temperature rises rapidly, the components in the powder metallurgy brake pad material are tightly bonded and not easy to separate, thereby inhibiting the thermal decay of the friction performance of the powder metallurgy brake pad material, thereby ensuring the excellent friction performance and low wear of the brake pad under high-speed braking. Therefore, Example 1 not only has a greater friction coefficient than Comparative Example 1 at a low speed of 80-160 km / h, but also has a greater friction coefficient than Comparative Example 1 at a high speed of 300-350 km / h, and the wear is also lower than Comparative Example 1.
[0046] Similarly, Example 2 also shows significant advantages over Comparative Example 2 in the test results.
[0047] In further comparison between Example 1 and Example 2, Example 1 further adds aluminum powder as a fluxing agent compared to Example 2. During the sintering process, aluminum melts earlier and infiltrates into the green body. The liquid surface tension of the molten aluminum causes adjacent raw material particles to move closer together and form a eutectic under the promotion of the molten aluminum, and the powder sintering is more dense. On the other hand, the residual aluminum is oxidized to form aluminum oxide under high-temperature friction, which promotes the formation of a friction film on the brake pad, and can increase the friction coefficient of the brake pad material at high speed and reduce the wear. Therefore, the average friction coefficient of Example 1 at low and high speed stages is greater than that of Example 2, and the wear is less than that of Example 2.
[0048] In addition, the amount of fluxing agent used for aluminum powder should not be too much. If too much is added, it will lead to the situation in Comparative Examples 3 to 4 - in Comparative Example 3, too much aluminum participates in the formation of eutectic during powder sintering, resulting in a decrease in the wear resistance of the powder metallurgy brake pad material; in Comparative Example 4, the proportion is higher, and the molten aluminum is affected by the sintering densification and seeps out and loads on the surface of the sintered body, resulting in a significant decrease in the friction coefficient.
[0049] Combining Example 1 and Example 3, it can be seen that the difference between Example 1 and Example 3 is that the iron powder used in Example 1 is foamed iron powder, and the average friction coefficient of the powder metallurgy brake pad material obtained in Example 1 is significantly improved compared with Example 3 in low-speed and high-speed braking, while the wear amount is only slightly reduced. Therefore, the use of foamed iron powder as the iron powder in this application can improve the friction performance of the powder metallurgy brake pad material.
[0050] In Example 1, ethanol is added as a diluent, polyethylene glycol is added as a binder, and N-β-hydroxyethylethylenediaminetriacetic acid is added during the ball milling process of the mixed raw materials. N-β-hydroxyethylethylenediaminetriacetic acid is soluble in ethanol, which inhibits and eliminates metal oxides produced by high temperature and extrusion stress during the ball milling process, especially iron oxides carried on the surface of iron powder or foamed iron powder, to prevent loose oxides from affecting the composition of the spray granulation and subsequent sintering eutectic body, so that the eutectic body has good strength after cooling and is more tightly combined with the unmelted solid powder particles, providing heat-resistant decay of the powder metallurgy brake pad material. Comparing Example 1 with Example 4, it can be verified that the average friction coefficient of Example 1 under high-speed braking is significantly better than that of Example 4, and the wear amount is lower than that of Example 4. On the other hand, the addition of N-β-hydroxyethylethylenediaminetriacetic acid has a correlation effect on the accelerator and other raw material components, and the amount of N-β-hydroxyethylethylenediaminetriacetic acid affects the positive or negative effect of N-β-hydroxyethylethylenediaminetriacetic acid on the overall benefit of powder metallurgy brake pad materials. Combined with Examples 5 to 8, it can be seen that the amount of N-β-hydroxyethylethylenediaminetriacetic acid in Examples 5 to 8 is constantly increasing, and Example 6 has an increased average friction coefficient and reduced wear compared to Example 5, and Example 7 has an increased average friction coefficient and reduced wear compared to Example 6, while Example 8 has a slight decrease in average friction coefficient compared to Example 7, and a considerable increase in wear, so the amount of N-β-hydroxyethylethylenediaminetriacetic acid in this application is preferably 0.3 to 0.5wt% of the mixture.
[0051] By comparing Example 1 with Examples 9-10, it can be seen that the powder metallurgy brake pad material in Example 1 is obtained by mixing and pressing powders of three particle sizes before sintering. The mixed combination has faster sintering densification and a higher degree of densification, which makes the powder metallurgy brake pad material have better heat decay resistance. The average friction coefficient of Example 1 during high-speed braking is greater than that of Examples 9-10 and the wear amount at the end of the program is less than that of Examples 9-10.
[0052] In combination with Example 1 and Examples 11 to 12, it can be seen that the powder metallurgy brake pad material of the present application has a raw material ratio of electrolytic copper powder, iron powder, tungsten, flaky graphite, molybdenum disulfide, zirconium dioxide, nano-silicon dioxide, tantalum carbide, and flux = (67-70):(12-17):(5-9):(12-18):(7-9):(5-8):(7-11):(5-8):(5-8), which can all achieve good heat-fading resistance and are better suitable for high-speed braking requirements.
[0053] Example 13 As attached Figure 1 As shown, a brake pad comprises a steel back 1 and a friction body 2 fixed on one side of the steel back 1.
[0054] The shape of the friction body 2 can be determined according to the actual design specifications, and is generally a hexagonal prism. The number and layout of the friction body 2 are determined according to the requirements of different train models in the actual design specifications.
[0055] As attached Figure 2 As shown, a fixed shaft 3 is fixed to the back of the friction body 3, and the fixed shaft 3 passes through the steel back 1 and is clamped with a retaining spring 4 to achieve the fixation of the friction body 2 and the steel back 1.
[0056] The friction body 2 is prepared from the powder metallurgy brake pad material in Examples 1 to 12.
[0057] The friction performance of this brake pad is resistant to heat decay. When the high-speed brake pad heats up rapidly, it still maintains an excellent friction coefficient and low wear, which is better suitable for and meets high-speed braking needs.
[0058] This specific embodiment is only an explanation of the present invention, and it is not a limitation of the present invention. After reading this specification, those skilled in the art can make non-creative modifications to this embodiment as needed, but as long as it is within the scope of protection required by the present invention, it will be protected by the patent law.
Claims
1. A powder metallurgy brake pad material, characterized in that: Obtained by powder sintering, it includes the following raw materials in parts by weight: 67-70 parts of electrolytic copper powder; 12-17 parts of iron powder; Tungsten 5-9 parts; 12-18 parts of flake graphite; Molybdenum disulfide 7-9 parts; 5-8 parts of zirconium dioxide; 7-11 parts of nano silicon dioxide; Tantalum carbide 5-8 parts.
2. The powder metallurgy brake pad material according to claim 1, characterized in that: The invention also comprises 5-8 parts of fluxing agent, wherein the fluxing agent is micron-grade aluminum powder.
3. The powder metallurgy brake pad material according to claim 1, characterized in that: The iron powder is foamed iron powder.
4. The method for preparing a powder metallurgy brake pad material according to any one of claims 1 to 3, characterized in that: The following steps are included: S1: weighing the raw materials according to the usage ratio and mixing them evenly to obtain a mixture; S2: Add the mixed material, medium and N-β-hydroxyethylethylenediaminetriacetic acid into a ball mill and grind them. S3: The slurry obtained by ball milling is spray dried to obtain powder particles. S4: filling the powder particles into a pressing mold and pressing to obtain a green body; S5: sintering the green body to obtain a powder metallurgy brake pad material; The medium is ethanol and polyethylene glycol, and the relative molecular weight distribution of polyethylene glycol is 1000-1200. The mass ratio of the mixture, ethanol and polyethylene glycol is 100:(56~65):(15~20).
5. The method for preparing a powder metallurgy brake pad material according to claim 4, characterized in that: The mass ratio of the mixed material to N-β-hydroxyethylethylenediaminetriacetic acid is 100:(0.3-0.5).
6. The method for preparing a powder metallurgy brake pad material according to claim 4, characterized in that: The particle size of S3 powder is 100~220μm.
7. The method for preparing a powder metallurgy brake pad material according to claim 4, characterized in that: The green body is compounded with powders of different particle sizes, and the particle size distribution is as follows: 210±10 μm particle size accounts for 46 wt %, 150±10 μm particle size accounts for 32 wt %, and 110±10 μm particle size accounts for 22 wt %.
8. A brake pad, characterized in that: The invention comprises a friction body (2), wherein the friction body (2) is made of the powder metallurgy brake pad material according to any one of claims 1 to 3.
Citation Information
Patent Citations
Copper-iron based powder metallurgy friction material for high-speed train braking and preparation method
CN107824783A
Powder metallurgy friction material for high-speed train braking and preparation method of powder metallurgy friction material
CN109518100A
Sintered friction material for railway vehicles, and method for producing same
CN110023521A
Brake material for medium-low-speed maglev train and preparation method of brake material
CN113073225A
Sintered friction material, composite copper alloy powder used therefor and manufacturing method thereof
EP0709476A1
Cited By
Powder metallurgy friction material and preparation method thereof, brake pad and hydro-generator
CN120961911A
Powder metallurgy friction material, method for manufacturing the same, brake pad, and hydroelectric generator
CN120961911B
